Development of Investment Strategy of Joint - stock Companies - Abdurazakova Nargiza Rikhsibaevna (Global Scientific Publishing, 2025)
This paper examines conceptual approaches, methodological foundations, and practical aspects of forming investment strategies in joint-stock companies, with a focus on modern economic conditions and the increasing importance of investment planning. The research analyzes strategic decision-making processes, classification of investment strategies, and key factors influencing their development. Particular attention is given to the investment behavior of companies in Uzbekistan, their needs for attracting capital, and the challenges they face due to insufficient strategic planning. The study employs theoretical analysis, structured interviews, and examination of recent statistical data. The findings highlight that clearly defined investment strategies improve companies’ competitiveness, financial stability, and ability to implement modernization programs. However, the lack of professional competencies and methodological tools limits their effectiveness.
Keywords: investment strategy; joint-stock company; investment planning; Uzbekistan